PENGUJIAN REAKSI INVESTOR TERHADAP PENGUMUMAN KABINET INDONESIA MAJU - Rexza Bramesta (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2020)
Capital markets are relevantly influenced by political event. This research aimed to analyze the market reaction on the announcement of cabinet of Indonesia Maju on October, 23 2019. Market reaction is measured by abnormal return and trading volume activity. This study used 44 companies from LQ45 group’s stock prices as population and used event study method to identify market reaction. The window event is 11 day long (t-5 – t+5). The statistical test used to test the hypotheses is simple t-test and paired sample test. The result of the statistical calculation of simple t-test showed there are no significant abnormal return around the date of the event. It means that investors do not respond to the event of newly cabinet announcement. The result of paired sample t-test showed there are no significant difference between the average abnormal return and trading volume activity obtained by sample companies listed in LQ45 index before and after the announcement of cabinet of Indonesia Maju.